2015
DOI: 10.1371/journal.pone.0144533
|View full text |Cite
|
Sign up to set email alerts
|

Expert Opinion on the Perceived Effectiveness and Importance of On-Farm Biosecurity Measures for Cattle and Swine Farms in Switzerland

Abstract: Biosecurity is crucial for safeguarding livestock from infectious diseases. Despite the plethora of biosecurity recommendations, published scientific evidence on the effectiveness of individual biosecurity measures is limited. The objective of this study was to assess the perception of Swiss experts about the effectiveness and importance of individual on-farm biosecurity measures for cattle and swine farms (31 and 30 measures, respectively). Using a modified Delphi method, 16 Swiss livestock disease specialist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 54 publications
3
56
0
1
Order By: Relevance
“…Pig production in Europe is highly heterogeneous with different biosecurity standards and productive levels (39, 81). Actions to prevent ASF introduction and spread should take into consideration the epidemiology of the disease, with especial focus on the virus resistance in the environment, routes of transmission, and excretion as well as the characteristics of the farming systems in place (5, 29, 38, 48, 58). As no vaccine for ASF is available, prevention of ASF relies upon implementing strict biosecurity measures to avoid potential contact between domestic pigs and ASF virus (35, 49, 58, 82).…”
Section: Resultsmentioning
confidence: 99%
“…Pig production in Europe is highly heterogeneous with different biosecurity standards and productive levels (39, 81). Actions to prevent ASF introduction and spread should take into consideration the epidemiology of the disease, with especial focus on the virus resistance in the environment, routes of transmission, and excretion as well as the characteristics of the farming systems in place (5, 29, 38, 48, 58). As no vaccine for ASF is available, prevention of ASF relies upon implementing strict biosecurity measures to avoid potential contact between domestic pigs and ASF virus (35, 49, 58, 82).…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 The criteria concerning humans were ranked as more important compared to the criteria 196 concerning animals; as an example "Treatment in humans" had a median score of 4.25, compared to 197 "Treatment in animals", which had a median score of 2 (Table 1) The method used in this study was first described for engineering projects (Rogers and Bruen, 208 1998), but has also been used in the veterinary field (Kuster et al, 2013). It allows for an equal 209 weighting of each experts' opinion through independent one-on-one interviews, thus reducing the risk 210 of over-or under-weighting an individual experts' opinion based on their behavior in a group 211 discussion.…”
Section: Domain 172mentioning
confidence: 99%
“…Biosecurity -defined as a series of measures aiming to stop disease-causing agents entering experiments in controlled conditions is not the ideal approach to biosecurity because of the 59 difficulty in extrapolating these findings to working farms (Kuster, et al, 2015). Studies of 60 farmers' attitudes to biosecurity have reported that the effectiveness of different measures is 61 very important to them; farmers do not want to take time to carry out practices that do not However, there are no studies that have explicitly looked into the practicality of biosecurity 66 measures on dairy farms.…”
mentioning
confidence: 99%